2016
DOI: 10.1016/j.jvoice.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Markerless Analysis of Articulatory Movements in Patients With Parkinson's Disease

Abstract: Summary: Objectives. A large percentage of patients with Parkinson's disease have hypokinetic dysarthria, exhibiting reduced peak velocities of jaw and lips during speech. This limitation implies a reduction of speech intelligibility for such patients. This work aims at testing a cost-effective markerless approach for assessing kinematic parameters of hypokinetic dysarthria. Study Design. Kinematic parameters of the lips are calculated during a syllable repetition task from 14 Parkinsonian patients and 14 age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Furthermore, in support of our findings, the 19 expressions analyzed by Cao et al include kissing, smiling, and raising the eyebrows [16]; lastly, (3) a study that was published using Kinect as a tool for the detection and rehabilitation of people with Parkinson's, which was considered as a highly valid tool due to its low cost and ease of use in the home [17]. It is difficult to compare studies with the same type of technology or similar to those that have been done, to date, among adults.…”
Section: Referencesupporting
confidence: 82%
“…Furthermore, in support of our findings, the 19 expressions analyzed by Cao et al include kissing, smiling, and raising the eyebrows [16]; lastly, (3) a study that was published using Kinect as a tool for the detection and rehabilitation of people with Parkinson's, which was considered as a highly valid tool due to its low cost and ease of use in the home [17]. It is difficult to compare studies with the same type of technology or similar to those that have been done, to date, among adults.…”
Section: Referencesupporting
confidence: 82%
“…The average root mean square error (RMSE) of the lip points with respect to an optoelectronic marker-based method ranged between 1 and 4 mm. The validity of the above video-based method was also demonstrated in a clinical population of individuals diagnosed with PD [12]. We were able to discriminate patients with PD from healthy controls, using lower lip movements during syllable repetitions.…”
Section: Introductionmentioning
confidence: 72%
“…The increasing availability of accurate, low-cost depth sensors, along with the development of efficient face alignment algorithms provide a great opportunity to introduce novel and intelligent systems in clinical environments [15], [16]. Previous studies demonstrated the feasibility of 3D video-based approaches for the assessment of motor speech disorders in patients with Parkinson's disease and amyotrophic lateral sclerosis (ALS) [17]- [19]. In this work, we aim to expand those findings to the automatic assessment of orofacial impairment in patients PS, evaluating facial movements during speech and non-speech tasks.…”
Section: Introductionmentioning
confidence: 99%